2020
DOI: 10.9734/asrj/2020/v3i430077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agronomic Biofortification of Sulphur and Boron on the Growth and Yield of Mustard (Brassica campestris L.) Crop

Abstract: Background and Objective: Sulphur and boron are found as most critical nutrient elements for the better growth and yield of mustard crop however no such concrete information for their uses in field production of this crop is yet to be reported. Therefore, an experiment was conducted to investigate the effect of agronomic biofortification of sulphur and boron nutrients on the growth and yield of mustard crop. Study Design: The experiment was laid out in a Randomized Complete Block Design (RCBD) with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…On the other hand, lowest yield was found in the genotype TKM-20-2 with the value of 4.23 q ha -1 . Awal et al (2014) reported significant variation in seed yield between the two species Brassica campestris and Brassica napus which is similar with the current study. Al-Juheishy et al (2021) revealed significant varietal differences in two rapeseed varieties in terms of seed yield which in corroboration to the findings of the current experiment.…”
Section: Quality Parameters and Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, lowest yield was found in the genotype TKM-20-2 with the value of 4.23 q ha -1 . Awal et al (2014) reported significant variation in seed yield between the two species Brassica campestris and Brassica napus which is similar with the current study. Al-Juheishy et al (2021) revealed significant varietal differences in two rapeseed varieties in terms of seed yield which in corroboration to the findings of the current experiment.…”
Section: Quality Parameters and Yieldsupporting
confidence: 91%
“…The findings were in corroboration with the findings of the current study. Awal and Fardous (2014) reported significant differences in plant height, number of primary branches and green leaves in different species of Brassica campestris. The result of the present study is in corroboration with the above findings.…”
Section: Morphological Parametersmentioning
confidence: 98%
“…The interaction effect due to sulphur (control, 15 kg ha -1 , 25 kg ha -1 and 35 kg ha -1 ) and boron (control, 1.5 kg B ha -1 and 2.5 kg B ha -1 ) on test weight of mustard seeds was found statistically significant. Comparative findings were detailed by Singh et al [33], Awal et al [34] and Rana et al [32]. ) was observed with the application of 35 kg S ha -1 (S 2 ).…”
Section: Seed Weight (Gm)mentioning
confidence: 86%